CSR's Role In Tax Avoidance: Impact Of Financial Performance And Green Accounting - Ivanda, Muhammad; Dwi Orbaningsih; Umi Muawanah (Jurnal Akuntansi, 2024)
This research examines how financial performance, green accounting, and corporate social responsibility (CSR) affect tax avoidance in IDX-listed mining companies between 2019 and 2022. This quantitative research employed multivariate correlational methods to analyse financial information from 23 coal mining companies. The variables are measured using the Effective Tax Rate (ETR) for tax avoidance, the GRI version 4 index for CSR, the Return on Assets (ROA) for financial performance, and the dummy technique for green accounting. Smart PLS uses Partial Least Square (PLS) for data analysis, including validity, reliability, and structural model assessments. The research found that financial success increases tax avoidance more than green accounting. CSR, which affects corporate tax avoidance, is also improved by green accounting. Corporate social responsibility mediates the relationship between green accounting and tax avoidance, not financial success and tax avoidance. This research shows that corporate social responsibility (CSR) mediates green accounting and tax avoidance.